PENGARUH INTERPERSONAL SKILL, SALESMANSHIP SKILL, TECHNICAL SKILL, DAN MOTIVASI TERHADAP KINERJA TENAGA PENJUALAN PADA PT UNITED TRACTORS TBK - Ilma Amalia; Makmun Riyanto; Umar Farouk (Politeknik Negeri Semarang, 2018)
This study aims to analyze the influence of interpersonal skill, salesmanship skill, technical skill, and work motivation on salesperson performance PT United Tractors Tbk. Research variables include: interpersonal skill (X1), salesmanship skill (X2), technical skill (X3), work motivation (X4) as independent variables, and salesperson performance (Y) as dependent variable. This study used multiple linear regression analysis. Samples are selected by using the method of purposive sampling. 55 salesperson are selected as samples in this study. Data collections techniques were using questionnaires, interview, observation, and documentary study. Based on the result of this study, interpersonal skill, salesmanship skill, technical skill, and work motivation have positive and significant influence on salesperson motivation. While the adjusted R square has value 65,9%, it means that interpersonal skill, salesmanship skill, technical skill, and work motivation give contribution to salesperson performance (Y) on 65,9% while 34.1% influenced by other variables which were not described in this study.